2023
DOI: 10.3390/diagnostics13172767
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and Histopathological Characteristics of Gastrointestinal Lymphoma: A Multicentric Study

Quang Trung Tran,
Thinh Nguyen Duy,
Bao Song Nguyen-Tran
et al.

Abstract: Background: Extranodal non-Hodgkin lymphoma (NHL) is more prevalent in the gastrointestinal (GI) tract than in other sites. This study aimed to determine the endoscopic characteristics of primary gastrointestinal non-Hodgkin lymphomas. Methods: We investigated 140 patients from three tertiary referral hospitals with primary malignant lymphoma of the gastrointestinal tract. Characteristics of the lesions were evaluated and analyzed using image-enhanced endoscopy, endoscopic ultrasound, and histopathology. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
2
0
2
Order By: Relevance
“…Meanwhile, the initial complaints of these patients were typically related to gastrointestinal symptoms, including abdominal pain, nausea, vomiting, altered bowel habits, and even intestinal obstruction and perforation. [ 12 ] Gastrointestinal endoscopy can identify most abnormal mucosa in a relatively early stage. However, relevant studies about ITCL are rare due to low incidence and lack of endoscopic findings specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the initial complaints of these patients were typically related to gastrointestinal symptoms, including abdominal pain, nausea, vomiting, altered bowel habits, and even intestinal obstruction and perforation. [ 12 ] Gastrointestinal endoscopy can identify most abnormal mucosa in a relatively early stage. However, relevant studies about ITCL are rare due to low incidence and lack of endoscopic findings specificity.…”
Section: Discussionmentioning
confidence: 99%
“…However, relevant studies about ITCL are rare due to low incidence and lack of endoscopic findings specificity. The few existing studies have reported the most common endoscopic abnormalities in intestinal lymphoma are the ulcerated lesion followed by eminence lesion, in addition to the diffusely infiltratively lesion and lymphomatous polyposis lesion et al [ 12 14 ] Ulcerated lesions may present multiple or solitary, various in size, different in shades, irregular in shape, the edges are flat or irregularly thickened. Yet those performance is often misdiagnosed as inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…Vì vậy không ngạc nhiên khi u lympho dạ dày -ruột là vị trí thường gặp nhất của u lympho ngoài hạch với tỉ lệ 30 -40% và là u ác tính thứ hai sau ung thư biểu mô tuyến khi tính ở dạ dày. Việc nhận định các tổn thương nghi ngờ u lympho dạ dày ruột trên nội soi được cho là có vai trò quan trọng nhằm tránh bỏ sót tổn thương và sinh thiết phù hợp [1]. Các nghiên cứu trước đây ở trong nước, đặc điểm mô học chủ yếu nhằm xếp loại theo công thức thực hành [2], [3].…”
Section: đặT Vấn đềunclassified
“…Việc vận dụng đúng các đặc điểm này trong thực hành sẽ giảm được các chỉ định hóa mô miễn dịch không cần thiết. Tuy nhiên, các tổn thương này nằm ở mô đệm vì vậy đối với các mảnh bấm sinh thiết ở tổn thương nghi ngờ u lympho dạ dày ruột cần đảm bảo độ sâu [1].…”
Section: đặC đIểm Mô Bệnh Học Và Hóa Mô Miễn Dịch 421 đặC đIểm Mô Lym...unclassified